Diffuse large B-cell lymphoma microenvironment displays a predominant macrophage infiltrate marked by a strong inflammatory signature - Serna, Leyre; Azcoaga, Peio; Brahmachary, Manisha; Caffarel, Maria M.; Braza, Mounia S. (Frontiers in Immunology, 2023)
Inflammasomes are cytosolic signaling hubs that promote the inflammatory response (i.e. an immune reaction to counteract threats in physiological conditions). Their potential role in lymphomagenesis remains to be elucidated. Depending on the context, innate immune cells, such as macrophages, may induce inflammation that contributes to the anti-tumor function; however, if uncontrolled, inflammation can promote cancer development. Here, we exploited bioinformatic tools, TCGA data, and tumor tissue samples from patients with diffuse large B-cell lymphoma (DLBCL), one of the most frequent non-Hodgkin lymphomas of B-cell origin, to investigate the distribution of the different immune cell subpopulations in DLBCL samples in order to characterize the immune landscape of their microenvironment. We found a clear prominence of macrophages in the DLBCL microenvironment. Particularly, the proportions of resting M0 and pro-inflammatory M1 macrophages were higher in DLBCL than spleen samples (controls). As each inflammasome has unique sensor activation and platform assembly mechanisms, we examined the expression of a large panel of inflammasome actors. We found that inflammasome components, cytokines and Toll-like receptors were upregulated in DLBCL samples, particularly in M0 and M1 macrophages, compared with controls. Moreover, their expression level was positively correlated with that of CD68 (a pan-macrophage marker). We confirmed the positive correlation between CD68 and IRF8 expression at the protein level in DLBCL tissue samples, where we observed increased infiltration of CD68- and IRF8-positive cells compared with normal lymph nodes. Altogether, our results highlight the inflammatory status of the DLBCL microenvironment orchestrated by macrophages. More work is needed to understand the complexity and potential therapeutic implications of inflammasomes in DLBCL.